Απελευθέρωση και τεκνοθεσία: μια νέα επιγραφική μαρτυρία από το ιερό του Ηρακλή Κυναγίδα στις Πέτρες Εορδαίας - Ναούμ Ελπινίκη; Πασχίδης Πασχάλης (Tekmeria, 2025)
An inscription recently found in the acropolis of the settlement of Petres in Eordaia and dated to 61/60 BC is published in this article. The inscription commemorates the liberation of a slave by a man, a woman and her son. The text provides interesting information on a number of topics, including family property, the liberation of slaves, the cult of Herakles Kynagidas, taxation pertaining to manumission, adoption (of manumitted slaves), the civic rights of manumitted persons, and, finally, the historical geography of northern Eordaia.